Surgical treatment following neoadjuvant chemoradiotherapy in locally advanced rectal cancer - Huang, Ming‐Yii; Huang, Ching‐Wen; Wang, Jaw‐Yuan (The Kaohsiung journal of medical sciences, 2020)
Colorectal cancer is a major public health problem worldwide, and locally advanced rectal cancer (LARC) is known for its poor prognosis. A multimodal treatment approach is the only method to achieve satisfactory local recurrence and survival rates in LARC. Determining which therapeutic modality for LARC has the most satisfactory influence on quality of life and disease outcome is still controversial. LARC treatment is subject to continuous advancement due to the development of new and better diagnostic tools, radiotherapy techniques, and chemotherapeutic agents. Herein, we review various therapeutic modalities for LARC from several aspects. In addition to radiotherapy techniques such as neoadjuvant chemoradiotherapy (NCRT), we discuss the progress of chemotherapy, appropriate time interval between NCRT and surgery, relationship between tumor location and NCRT efficacy/safety, wait‐and‐watch policy, and predictors of treatment response following NCRT. Because of the controversies and unanswered questions regarding NCRT treatments for LARC, additional investigations are required to determine which therapeutic approach is the most feasible for LARC patients.